Who is feeding on the pear psylla? Applying molecular ecology for the biological control of Cacopsylla bidens. Issue 4 (2nd October 2022) - Valle, D.; Cabrera, N.; Clavijo, F.; Mujica, V.; Gonzalez, A.; Siri, M.; Lavandero, B.
Abstract: Biological control is an alternative strategy to control Cacopsylla bidens . The aim of this study was to untanglethe trophic network involving C. bidens as prey. Molecular techniques along with predator activity surveys were employed to evaluate predation on psylla. Feeding on C. bidens was detected for five predators: Chrysoperla externa, Chrysopidae sp ., Hemerobiidae sp ., Harmonia axyridis and Cycloneda sanguinea . All these predators begin to feed earlier in the season, apart from C. externa which fedds from the third psylla generation. These results will allow the development of strategies to increase the presence of these predators in the orchards.